Design of a 1-phase Axial Flux Type Generator with a Variation of Winding on a Star-Shaped Stator - Muhammad Ikhsanudin; Irwan Novianto; Bledug Kusuma Prasaja (PTE FTK UIN Ar-Raniry, 2024)
A single-phase axial flux generator with a star-shaped stator is required to explore the optimal use of rainwater energy as a renewable energy source. Untuk eksperimen, jumlah coils dan diameternya diubah. 25 coils dan 50 coils with 0.4 mm diameter and 25 coils and 40 coils with 0.5 mm diameter were designed. Generator performance will be tested under load and no load conditions at 600 rpm to 2000 rpm. The test results indicate that, for a single-phase axial generator running at 2.4W output conditions, increasing the number of windings impacts the voltage induced by the generator and that the number of stator windings influences the quantity of induced voltage, current, and power. Test findings with various winding variations, employing a 4.8V 0.5A or 2.4W light bulb load, demonstrate that an increase in winding count leads to an increase in electrical output